2020
DOI: 10.3897/zookeys.935.37138
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy reveals three new taxa within the Tylototriton asperrimus complex (Caudata, Salamandridae) from Vietnam

Abstract: The Tylototriton asperrimus complex from northern Vietnam is reviewed based on morphological comparisons and analysis of the mitochondrial marker NADH dehydrogenase subunit 2 (ND2). Based on molecular divergences, which were revealed to be higher than in other congeners, in concert with morphological differences, two new species and one subspecies are described herein: Tylototriton pasmansisp. nov. differs from T. asperrimussensu stricto by 3.2 to 3.6 % genetic divergence and a combination of distinct morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…The salamandrid genus Tylototriton Anderson, 1871 (colloquially known as crocodile newts) currently includes 31 recognized species, inhabiting montane forest areas throughout the Asian monsoon climate zone from eastern Himalaya, southern and central China including Hainan Island, to northern Indochina including northern Vietnam, Laos, northern Thailand, and Myanmar (Wang et al 2018, Bernardes et al 2020, Frost 2021). The genus is traditionally partitioned into two subgenera: Tylototriton sensu stricto is characterized by the presence of orange spots on the head, dorsum, tail, or sides TAPROBANICA VOL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The salamandrid genus Tylototriton Anderson, 1871 (colloquially known as crocodile newts) currently includes 31 recognized species, inhabiting montane forest areas throughout the Asian monsoon climate zone from eastern Himalaya, southern and central China including Hainan Island, to northern Indochina including northern Vietnam, Laos, northern Thailand, and Myanmar (Wang et al 2018, Bernardes et al 2020, Frost 2021). The genus is traditionally partitioned into two subgenera: Tylototriton sensu stricto is characterized by the presence of orange spots on the head, dorsum, tail, or sides TAPROBANICA VOL.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent phylogenetic studies also demonstrated that our knowledge on taxonomic diversity of the genus Tylototriton is still far from complete, indicating the presence of numerous undescribed morphologically cryptic lineages, which actually might represent independent species (Wang et al 2018, Than Zaw et al 2019. The amount of undescribed diversity appears to be especially high in the T. asperrimus group of the subgenus Yaotriton (Bernardes et al 2020, Li et al 2020. The number of species of Tylototriton in Vietnam is high, with seven species of this genus having been recorded so far for the country, namely T. anguliceps Le, Nguyen, Nishikawa et al 2015, T. notialis Stuart, Phimmachak, Sivongxay & Robichaud, 2010, T. pasmansi Bernardes, Le, Nguyen et al, 2020, T. cf.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, by employing a molecular dating method, Liang et al (2018) estimated that the latest speciation events among tiger geckos took place approximately 2.8-2.9 Ma, in the late Pliocene, between G. yamashinae-G. orientalis, and G. huuliensis-G. luii. It is likely that the global warming during the Pliocene promoted the diversification in the genus, as also reported in the crocodile newts (genus Tylototriton Anderson, 1871) in Asia (Bernardes et al 2020). Thus, the genus Goniurosaurus might offer a unique opportunity to investigate mechanisms of speciation and evolutionary adaptation, that are expected to highly correlate with a pre-dominantly allopatric mode of diversification.…”
Section: Taxonomic Reviewmentioning
confidence: 80%